Canva Application Development for Distance Learning on Arabic Language Learning in MTs Thawalib Tanjung Limau Tanah Datar - Adam Mudinillah; Salam, Muhammad Yusuf (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2021)
This study aims to find out the effectiveness and practicality of Canva applications that can be used online in Video format. The video is developed as a learning medium during distance learning for Arabic language learning. The method used in this study is the R & D (Research and Development) method by following the Borg and Gall models. This research model has ten steps of development, these are: 1) Research and information collection, 2) Planning, 3) Develop a preliminary form of product, 4) Preliminary field testing, 5) Main product revision, 6) Main field testing, 7) Operation product revision, 8) Operational field testing, 9) Final product revision, 10) Dissemination and implementation. This study only comes to the sixth step which at that step focuses only on field trials. The results of the field trials are the results of content verification on audiovisual learning media using the Canva application for distance learning with an average of 4.66 or in an excellent category with a maximum score of 5.00. While the average field test score on students' responses to learning media using the Canva app for distance learning is 3.78 and the maximum score is 5.00.